2021
DOI: 10.3389/fpls.2021.800030
|View full text |Cite
|
Sign up to set email alerts
|

Effectors of Root-Knot Nematodes: An Arsenal for Successful Parasitism

Abstract: Root-knot nematodes (RKNs) are notorious plant-parasitic nematodes first recorded in 1855 in cucumber plants. They are microscopic, obligate endoparasites that cause severe losses in agriculture and horticulture. They evade plant immunity, hijack the plant cell cycle, and metabolism to modify healthy cells into giant cells (GCs) – RKN feeding sites. RKNs secrete various effector molecules which suppress the plant defence and tamper with plant cellular and molecular biology. These effectors originate mainly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 157 publications
(242 reference statements)
0
12
0
Order By: Relevance
“…This evidence suggests that MJ-10A08 is secreted during the stages of nematode invasion and migration in the roots, and plays a core role in the parasitic stage. Host-delivered RNAi has been well utilised in previous investigations of the molecular function of effectors from RKN (Vieira & Gleason, 2019;Jagdale et al, 2021). In our study, the expression of Mj-10A08 was reduced in the nematodes isolated from host-delivered RNAi transgenic plants.…”
Section: Discussionmentioning
confidence: 62%
“…This evidence suggests that MJ-10A08 is secreted during the stages of nematode invasion and migration in the roots, and plays a core role in the parasitic stage. Host-delivered RNAi has been well utilised in previous investigations of the molecular function of effectors from RKN (Vieira & Gleason, 2019;Jagdale et al, 2021). In our study, the expression of Mj-10A08 was reduced in the nematodes isolated from host-delivered RNAi transgenic plants.…”
Section: Discussionmentioning
confidence: 62%
“…Giant cells are multinucleated, larger cells that normally develop in plant vascular tissues, and nourish nematodes by redistributing the metabolites of plants ( Sreekavya et al., 2019 ). The J2 further molt three times, transitioning to the third-stage (J3) and fourth-stage (J4) until becoming sexual adults ( Jagdale et al., 2021 ). Due to a malfunctioning stylet, the J3 and J4 stage nematodes cannot feed ( Rashidifard, 2019 ).…”
Section: Life Cyclementioning
confidence: 99%
“…Cyst nematodes induce the syncytium by dissolving cell-wall of neighboring cells and fusing their protoplasts ( Zhang et al, 2017 ). Root-knot nematodes recruit the progenitor cell, induce cell enlarge and repeated mitosis without cytokinesis, and eventually form a giant cell ( Jagdale et al, 2021 ). Thus, reprogramming host cell differentiation is an essential virulence strategy for nematode survival.…”
Section: Altering Host Growth and Development As A Virulence Strategymentioning
confidence: 99%
“…Expressing SAP54, an effector of Aster Yellows phytoplasma strain Witches’ Broom (AY-WB), was sufficient to induce phyllody in Arabidopsis ( Aurin et al, 2020 ). Further studies showed that SAP54 alters the host plant reproductive and floral development by degrading a group of type II MADS-domain transcription factors (MTFs) regulating the floral transition and floral organ development ( Jagdale et al, 2021 ). Arabidopsis radiation-sensitive-23 (RAD23) family proteins, RAD23C, and RAD23D, physically interact with SAP54 and are required for the degradation of host MTFs and phytoplasma-induced phyllody ( MacLean et al, 2014 ).…”
Section: Altering Host Growth and Development As A Virulence Strategymentioning
confidence: 99%